Why cognitive skills matter for development and what explains their variation - Keskin, Huseyin Atakan (2019)
Growth theories and the role of human capital formation in development remain widely-discussed topics in the field of education economics. While a plethora of studies that use school enrollment rates as a proxy for human capital fail to explain the variation in per-capita GDP growth, more recent work in the economics of education shows that cognitive skills are essential for development. How these skills are formed, however, is less clear and should be investigated. This dissertation examines whether cognitive skills, measured by science and mathematics, explain human development in Sudan. Drawing on the 2018 Sudanese National Learning Assessment, part of the Basic Education Recovery Project of World Bank (2019a), the questions are: Do cognitive skills matter for development? If so, what explains their variation? The findings, achieved through correlation analyses between state-level poverty rates and science & mathematics achievement, show a robust significant relationship. Additionally, multivariate OLS models indicate that components of Cunha and Heckman (2007) theory on skill formation such as subsequent achievement, parental and environmental factors and a student asset index created with a machine-learning algorithm explain the variation in science achievement.